Complex educational design and teacher development:: an articulation grounded on complexity and transdisciplinarity - Costa, Solange Lopes Vinagre; Freire, Maximina Maria (The ESPecialist, 2024)
This article discusses how complex educational design (FREIRE, 2013) can be used as a framework for creating teacher development courses grounded on complexity and transdisciplinarity. Courses like these aim to provide educational experiences that consider the complex characteristics of life and that may help teachers foster the formation of 21st century planetary citizens. To illustrate such possibility, the main attributes of a remote English teacher development course, based on the mentioned design, are presented, as well as some results of the research it was part of.